Low incidence of pelvic sepsis following Hartmann’s procedure for rectal cancer: a retrospective multicentre study - Elin Mariusdottir; Fredrik Jörgren; Amelia Mondlane; Jens Wikström; Marie-Louise Lydrup; Pamela Buchwald (BMC Surgery, 2022)
Abstract Background Results of previous studies regarding pelvic sepsis after Hartmann’s procedure (HP) for rectal cancer have been inconsistent and few studies report the risk factors. This study aimed to investigate the incidence of pelvic sepsis after HP, identify risk factors and describe when as well as how pelvic sepsis was diagnosed and treated. Methods Data were collected from the Swedish Colorectal Cancer Registry on all patients undergoing HP for rectal cancer in the county of Skåne from 2007–2017. Patients diagnosed with pelvic sepsis were compared with patients without pelvic sepsis and risk factors for developing pelvic sepsis were analysed in a multivariable model. Results A total of 252 patients were included in the study, with 149 (59%) males, and a median age of 75 years (range 20–92). Altogether, 27 patients (11%) were diagnosed with pelvic sepsis. Risk factors for developing pelvic sepsis were neoadjuvant radiotherapy (OR 7.96, 95% CI 2.54–35.36) and BMI over 25 kg/m2 (OR 5.26, 95% CI 1.80–19.50). Median time from operation to diagnosis was 21 days (range 5–355) with 11 (40%) patients diagnosed beyond 30 days postoperatively. The majority of cases 19 (70%) were treated conservatively and none needed major surgery. Conclusion Pelvic sepsis occurred in 11% of patients. Neoadjuvant radiotherapy and higher BMI were significant risk factors for developing pelvic sepsis. Forty percent of patients were diagnosed later than 30 days postoperatively and most patients were successfully treated conservatively. Our findings suggest that HP is a valid treatment option for rectal cancer when anastomosis is inappropriate, even in patients receiving neoadjuvant radiotherapy.